Mycelium production rate in Lentinula edodes as an effect of depth and supplementation of the substrate - Rossi, Ivan Henrique; Monteiro, Antonio Carlos; Machado, José Octávio (Pesquisa Agropecuaria Brasileira, 2001)
The objective of the present study was to assess the rate of mycelium development of Lentinula edodes (Berk.) Pegler as an effect of depth and supplementation of the sugar cane bagasse substrate with different amounts of rice bran and sugar cane molasses. The experimental design consisted in a 7 x 2 factorial scheme (seven levels of bran or molasses x two growth phases) using autoclavable glass flasks to keep the substrates. The proportions of rice bran tested were: 0, 10, 15, 20, 25, 30 and 40% (dry weight/bagasse dry weight), and the concentrations of sugar cane molasses were: 0, 10, 20, 30, 40, 50 and 60 g/kg substrate. Graph paper strips externally sticked to the flask were used to measure the mycelial development. To differentiate the growth as a function of depth, the mycelial development was divided into two phases: an initial one (upper half of the flask) and a final one (lower half). The rate of mycelium formation was always higher in the early growth than in the final phase regardless of the amount of supplement. High bran proportions reduced the rate of mycelium formation, especially during the final phase, and sugar cane molasses did not affect growth rate.